Assessing behavioural and social responses to an eco-mooring trial for Zostera marina conservation management in Torbay, Southwest England. (1st October 2019) - Parry-Wilson, Hannah M.; Rees, Sian E.; Leather, Harrison; Cole, Rachel; Rugg, Clare; Attrill, Martin J.
Abstract: Seagrass beds are critically important habitats delivering a range of ecosystem service benefits that support human wellbeing. They are, however, declining globally at an unprecedented rate. The damaging effects on Zostera marina (Common Eelgrass) seagrass beds in UK waters from mechanical recreational boating activities, namely anchoring and traditional swing mooring scour, suggest that measures of implementing management to mitigate human impacts need prioritising. Eco-moorings, a design that reduces the abrasion pressure of anchoring and mooring on the seabed, are such a mitigation method. In the UK, limited test sites and a lack of social acceptance of the technology compounds the limited uptake of eco-moorings to date. To advance the evidence base, this study focusses on a bespoke eco-mooring design deployed in 2017 to protect seagrass beds within a popular anchorage in Southwest England. We assess the behavioural and social responses of recreational boaters to the trial eco-mooring through 1) mapping of boating activity pre- and post-deployment and 2) structured questionnaires both on-site and online to local and national audiences respectively. Results of mapped boating activity demonstrated a shoreward distribution shift of anchoring away from the deployed eco-mooring, with 45.4% of all anchoring vessels directly within or within a range of potential influence of the seagrass bed. Through the deployment of the eco-mooring (where no mooring previously existed), an estimated additional 20% of anchoring pressure was alleviated from the seagrass bed. A total of 89.6% of on-site respondents reacted positively to the prospect of further eco-moorings being deployed locally. When questioned, 74.6% of on-site and 82.8% of online respondents demonstrated a preference for the physical action of mooring a vessel over anchoring. This suggests that implementation of eco-moorings in seagrass-dense regions could successfully alleviate anchor damage, especially where over half of respondents indicated an awareness of seagrass presence prior to anchoring their vessel and/or hesitance to cease visiting preferential anchoring sites (sheltered bays). This study recommends targeting conservation guidance at the powerboat community, the dominant group anchoring/mooring in the study area and identified as not currently engaged in seagrass education campaigns. It is proposed that management introduce incentives such as free of charge eco-moorings and/or anchoring charges in Marine Protected Areas/Voluntary No Anchor Zones to conserve and recover seagrass and other sensitive seabed habitats nationally. Highlights: Of all vessels, 45.4% anchored within or within range of influence of the mapped seagrass bed. Eco-mooring use alleviated an estimated 20% of anchoring within range of the seagrass bed. On-site (74.6%) and online (82.8%) respondents demonstrated a preference for mooring over anchoring. This study highlighted hesitance from boaters to cease visiting preferential anchoring sites. Top-down management should urgently deploy eco-moorings with free-of-charge incentives.